ICT self-efficacy, self-efficacy for teamwork, and collegial collaborations: an exploratory study of elementary school teachers’ ICT uses in inquiry-based learning in Japan - Yonezawa, Takashi; Nakai, Yuka (Frontiers in Education, 2024)
Inquiry-based learning, an educational approach that is gaining international recognition, emphasizes active engagement and deeper understanding. Despite its benefits, integrating information and communication technology (ICT) into inquiry-based learning remains a challenge, often hindered by factors such as teachers' confidence in ICT use and organizational support. This study aimed to explore the relationship between the utilization of ICT in inquiry-based learning and various factors including ICT self-efficacy, lack of ICT resources at school, teachers' collaboration in using ICT, and self-efficacy for teamwork. A web questionnaire was administered to 324 full-time elementary school teachers in Japan, assessing their perceptions of ICT use in inquiry-based learning, ICT self-efficacy, collaboration, teamwork self-efficacy, and school ICT resources. Statistical analyses, including exploratory factor analysis and multiple regression, were employed to examine the relationships between variables. The findings revealed significant positive associations between ICT use in inquiry-based learning and ICT self-efficacy for instructional purposes, teachers' collaboration in using ICT, and self-efficacy for teamwork. However, the relationship with the lack of ICT resources at school was not statistically significant. These results underscore the importance of fostering teachers' self-efficacy and promoting collaborative practices to enhance ICT use in inquiry-based learning. Furthermore, the study highlights the need for ongoing support and resources to facilitate the effective utilization of ICT in educational settings.